PENERAPAN TEKNIK FOAM MAT DRYING DAN KONSENTRASI MALTODEKSTRIN PADA KOPI INSTAN MANGROVE (Rhizophora stylosa) - Mohammad Firdaus; Rieny Sulistijowati; Wila Rumina Nento (Pattimura University, 2026)
This study aimed to determine the effect of foam mat drying technique and maltodextrin concentration on the physicochemical characteristics of instant mangrove coffee made from Rhizophora stylosa fruit. The study employed a Completely Randomized Design with six level of different maltodextrin concentration (11%, 14%, 17%, 20%, 23%, 26%) and each with three replications. The parameters analysis included density, solubility, dissolution time and moisture content. The results showed that maltodextrin concentration affected the physicochemical properties of the product, as indicated by a bulk density of 0.39 g/mL, solubility of 68,05%, dissolution time of 58,44 seconds and moisture content of 2,56%. Higher maltodextrin concentration increased solubility and reduced dissolution time. The foam mat drying technique combined with appropriate maltodextrin addition has the potential to produce high-quality instant mangrove coffee. Keywords: foam mat drying, maltodextrin, instant coffee